THE ESSENCE OF THE LAW ON BANK SECRET OF THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2022)
This article describes banking activity, which forms the basis of the financial sector and is considered one of the economic drivers of the state. In this article banks and banking activities of the Republic of Uzbekistan, regulation of the database constituting bank secret, what information constitutes bank secret is discussed. Activities related to obtaining and working with this category of information are analyzed on the basis of legislation
Keywords: banking activity; confidentiality legislation; client and bank information; finance